The COLLISION OF VIRTUAL REALITY BASED INSTRUCTION ON BIOLOGY STUDENTS MOTIVATION IN SECONDARY SCHOOL IN ILORIN, KWARA STATE: COLLISION OF VIRTUAL REALITY BASED INSTRUCTION ON BIOLOGY STUDENTS MOTIVATION IN SECONDARY SCHOOL IN ILORIN, KWARA STATE - Abidoye, Dr. Florence Omosholape; Aladesuyi, David Adeyemi; Afolabi, Dr. kayode Ojo (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This study examined biology students' motivation was affected by virtual reality (VR) at secondary schools in Ilorin, Kwara State. 544 pupils from 20 secondary schools that were purposefully chosen made up the sample. Data is gathered using the Instructional Materials Motivation Survey (IMMS), which is based on Keller's ARCS motivation paradigm. Descriptive and inferential statistics (mean and standard deviation), and t-test were used to analyze the collected data. The findings of the study unveiled that the implementation of virtual reality-based instruction has a significant impact on the motivation of biology students in secondary schools. Moreso, the attention and satisfaction categories had the greatest favorable replies, indicating that VR has a considerable impact on students' motivation, according to the results. There are gender disparities in attention, with females showing higher levels. Therefore, the study suggests incorporating virtual reality (VR) into teaching methods and creating inclusive VR experiences that appeal to both male and female students.